Spin regulation induced CO2 reduction catalytic material as well as preparation and application methods thereof

By synthesizing and controlling the spin state of the iron metal tetracore cation cluster, the problem of low CO2 reduction efficiency of existing photocatalysts is solved, and the effect of significantly improving CO2 photoreduction activity is achieved.

CN119775215AActive Publication Date: 2025-04-08CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411986602.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing photocatalysts have low efficiency in CO2 reduction and have limited strategies to regulate spin states, making it difficult to effectively improve catalytic performance.

Method used

By synthesizing a ferrometal tetracore cation cluster, self-assembly technology is used to regulate the coordination microenvironment of the Fe site and change its spin state, thereby improving the adsorption and activation ability of CO2.

Benefits of technology

The activity of CO2 photoreduction reaction was significantly improved, and the CO yield could reach 9.53 mmol g-1 within 4 hours, which was 4 times that of the low-spin metal grid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775215A_ABST
    Figure CN119775215A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of efficient catalytic materials for carbon dioxide photo-reduction reaction, and relates to a spin regulation and induction CO2 reduction catalytic material as well as a preparation method and an application method thereof. The molecular formula of the single crystal structure of the material is [Fe < 4 > (dopz) < 4 >] (CF3SO3) < 4 >. 3MeCN. H2O or [Fe < 4 > (dspz) < 4 > (CF3SO3) < 4 >. EtOH. 3H2O. Wherein the dopz is 2, 2 '-bis (pyrazine) hydrazine carbonate; and dspz is 2, 2 '-dipyrazine thiohydrazine. The self-spinning state of the metal center is accurately controlled by adjusting the coordination environment of the Fe site, so that the self-spinning state of the catalytic center is converted from Fe < 3 + > low self-spinning to Fe < 3 + > high self-spinning, the activity of the cluster in the CO2 photoreduction reaction is remarkably improved, the CO yield can reach 9.53 mmol g <-1 > after light irradiation is performed for 4 hours, and the photocatalytic performance can be effectively adjusted by adjusting and controlling the self-spinning state of the metal center.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high-efficiency catalytic materials for photoreduction of carbon dioxide reaction, and relates to a spin-regulated CO2 reduction catalytic material and a preparation and application method thereof. Background Art

[0002] With the deterioration of the environment and the depletion of fossil fuels, new clean, renewable and sustainable resources are urgently needed to replace fossil fuels. Photocatalysis has been widely explored in water splitting, CO2 reduction, N2 fixation and pollutant degradation, and is considered to be one of the important ways to achieve sustainable energy supply and environmental remediation. Unfortunately, the photocatalytic efficiency of photocatalysts for large-scale practical applications is still relatively low so far. The catalytic efficiency of photocatalysts is affected by several key factors, such as: (1) light harvesting ability; (2) substrate adsorption and activation energy; (3) separation and transportation of photocarriers. It is worth noting that the development of suitable photocatalysts is crucial for the efficient execution of the catalytic process. It is well known that the performance of photocatalysts depends largely on the intrinsic properties of their electronic states, such as the spin states of transition metal sites. In the past few years, efforts have been made to develop various strategies to regulate the spin states of metal centers to further improve their catalytic performance.

[0003] The electronic structure determines the properties of the material, among which spin is an important inherent characteristic of electrons. It can reflect the electronic structure of the catalyst and dominate the chemical behavior of the catalyst.

[0004] However, there are very limited examples of spin regulation in photocatalysis, especially photocatalytic CO2 reduction, which may be due to the great challenges of regulating spin states in common photocatalysts. Currently, spin state regulation in multiphase photocatalysts is mainly limited to the generation of structural vacancies and elemental doping. Unfortunately, vacancies and dopants are not necessarily catalytically active for CO2 reduction, and sometimes vacancies are even recombination centers for electrons and holes. At the same time, the distribution of vacancies and dopants in the catalyst is not uniform, and only local spin states change. Therefore, the generation of vacancies and elemental doping in photocatalysts remains a challenge, not only in terms of precise manufacturing, but also in establishing the relationship between spin regulation and photocatalysis. Summary of the invention

[0005] The present invention provides a spin-regulated CO2 reduction catalytic material and a preparation and application method thereof, which relates to a tetranuclear cation cluster. The material regulates the spin state of the Fe site by changing the coordination microenvironment without necessarily changing the oxidation state of Fe. This regulation leads to differences in charge separation efficiency and changes in the adsorption and activation capabilities of CO2.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a spin-regulated induced CO2 reduction catalytic material, the single crystal structure molecular formula of the material is: [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O or [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O; wherein dopz is 2,2'-bipyrazine carbonate hydrazine; dspz is 2,2'-bipyrazine thiohydrazine.

[0008] The second aspect of the present invention provides a method for preparing a spin-regulated CO2 reduction catalytic material, the method comprising:

[0009] S1. Preparation of organic ligand dopz: put dihydrazide carbonate in a reaction bottle, add ethanol, stir to dissolve, then add 2-acetylpyrazine, then drop glacial acetic acid, heat and stir, after the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a white powder product;

[0010] The reaction formula is as follows:

[0011]

[0012] Under the catalysis of glacial acetic acid, the nitrogen atom (nucleophilic center) of the hydrazine group attacks the carbonyl carbon to form an unstable addition intermediate: the addition intermediate undergoes a dehydration reaction under acidic conditions, and the hydroxyl group (-OH) and the adjacent proton (H + ) is removed to form a carbon-nitrogen double bond structure connected by bipyrazine, and the target product dopz is generated after dehydration.

[0013] Preferably, the molar ratio of carbonate dihydrazide to 2-acetylpyrazine is 1:2, and the volume ratio of ethanol to glacial acetic acid is: 49.9mL-50.1mL: 0.15mL-0.25mL. In the reaction, the hydrazide group (-NH-NH2) of carbonate dihydrazide provides two active sites per molecule, and the carbonyl group of 2-acetylpyrazine is the electrophilic center of the reaction. The molar ratio of 1:2 ensures that each hydrazide group can fully react, and there will be no extra reaction sites, thereby reducing the occurrence of side reactions.

[0014] As a solvent, ethanol can dissolve reactants and intermediates well, provide a uniform reaction environment, and avoid reactant aggregation or excessive local concentration; the amount of glacial acetic acid (0.15 mL to 0.25 mL) is sufficient to protonate the carbonyl group in 2-acetylpyrazine, increase its electrophilicity, and thus accelerate the nucleophilic addition reaction.

[0015] Furthermore, the time of the reaction under heating reflux stirring is 5 to 6 hours, and the temperature is 78° C. to 82° C. 78° C. to 82° C. is close to the boiling point of ethanol (about 78.5° C.), ensuring that the solvent is in a reflux state, providing a constant high temperature environment for the reaction, and the temperature can effectively stimulate the reaction energy barrier between dihydrazide carbonate and 2-acetylpyrazine, promote the smooth progress of nucleophilic addition and dehydration condensation reactions, and the reaction time of 5 to 6 hours can ensure that all reactants react fully, reduce the residue of unreacted raw materials, and improve the yield of the target product dopz.

[0016] S2. Preparation of organic ligand dspz: put thiomethylhydrazine into a reaction bottle, add ethanol, stir to dissolve, then add 2-acetylpyrazine, then drop glacial acetic acid, heat and stir, after the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a light green powder product;

[0017] The reaction formula is as follows:

[0018]

[0019] The nitrogen atom of the hydrazine group (-NH-NH2) in thiomethylhydrazine attacks the carbonyl carbon (C=O) of 2-acetylpyrazine. The glacial acetic acid protonates the carbonyl oxygen, which enhances the electrophilicity of the carbonyl carbon. After nucleophilic addition, an intermediate containing a hydroxyl group (-OH) and a thiocarbonyl group (C=S) is formed. The addition intermediate undergoes a dehydration reaction, and the hydroxyl group (-OH) reacts with the proton (H + ) combines, removes a molecule of water, and generates a C=N double bond at the same time: the reaction continues, and another molecule of 2-acetylpyrazine undergoes a second nucleophilic addition reaction with the hydrazine group (-NH-NH2) in the product to form a bipyrazine structure, and finally generates the target product dspz, in which two molecules of 2-acetylpyrazine are connected by the hydrazine group to form the core structure of 2,2'-bipyrazinethiohydrazine.

[0020] Preferably, the molar ratio of thiomethylhydrazine to 2-acetylpyrazine is 1:2. The thiomethylhydrazine molecule contains two active sites (-NH-NH- and -C=S). Each active site requires a molecule of 2-acetylpyrazine to participate in the reaction. The molar ratio of 1:2 can ensure that each thiomethylhydrazine molecule reacts fully with two molecules of 2-acetylpyrazine to form a bipyrazine structure.

[0021] The volume ratio of ethanol to glacial acetic acid is: 49.9mL-50.1mL: 0.15mL-0.25mL. Ethanol, as a solvent, can dissolve thiomethylhydrazine and 2-acetylpyrazine, and improve the distribution uniformity of the reactants in the solution. The amount of glacial acetic acid is optimized to effectively remove the carbonyl group in 2-acetylpyrazine, improve its electrophilicity, and accelerate the nucleophilic addition reaction. The amount of glacial acetic acid is moderate to avoid excessive acidity leading to degradation of thiomethylhydrazine or intermediates.

[0022] Furthermore, the heating reflux stirring reaction time is 5 to 6 hours, and the temperature is 78° C. to 82° C.

[0023] S3. Preparation of complex: Add the ligand dopz prepared in step S1 or the ligand dspz prepared in step S2 into a beaker containing acetonitrile / acetonitrile and ethanol, stir to dissolve, add metal salt Fe(CF3SO3)2, mix and stir evenly at room temperature, filter, and let stand for one week to obtain complex crystals.

[0024] Furthermore, the stirring temperature is room temperature (25±2°C).

[0025] Among them, in step S3, two complexes are prepared due to different raw materials. When the ligand dopz is used to prepare the complex, the ligand dopz is added to a beaker filled with acetonitrile, stirred to dissolve, and the metal salt Fe(CF3SO3)2 is added, mixed and stirred evenly at room temperature to obtain a wine red clear liquid. After filtering, the filtrate is evenly divided into test tubes, placed in a wide-mouth bottle filled with isopropyl ether, and allowed to stand for one week to obtain black square crystals, which are the complex [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O;

[0026] Specifically, the ligand dopz was completely dissolved in acetonitrile and mixed with the iron salt Fe(CF3SO3)2. 2+ ions gradually formed coordination bonds with the pyrazine ring nitrogen atom (N) in the dopz molecule. Under stirring conditions at room temperature, the four Fe 2+ The ion and four dopz ligands form a [2×2] metal framework structure through self-assembly; the dopz ligand connects Fe 2+ ions, each Fe forms a N4O2 coordination environment: the coordination solution (wine red clear solution) is filtered and divided into test tubes, which are placed in a wide-mouth bottle filled with isopropyl ether. The miscibility between isopropyl ether and acetonitrile is limited, resulting in the slow evaporation of acetonitrile, and the solution gradually reaches a supersaturated state. In the supersaturated state, the [Fe4(dopz)4] core and CF3SO 3- Anions, acetonitrile (MeCN) molecules and water molecules together form a crystal structure, and after a week, black square crystals are generated.

[0027] Preferably, the molar ratio of dopz to Fe(CF3SO3)2 is 1:1; the usage ratio of acetonitrile to dopz is: 39mL-41mL: 0.19mmol-0.21mmol. The molar ratio of 1:1 means that each Fe 2+The ion and a dopz ligand can be perfectly matched to avoid excess or deficiency of reactants. The amount of acetonitrile used as a solvent has been optimized. 39mL~41mL of acetonitrile provides sufficient dissolution space for 0.19mmol~0.21mmol of dopz, ensuring that the reactants are evenly distributed in the solution. A sufficient amount of solvent can avoid excessive concentration of local reactants, thereby reducing the occurrence of side reactions.

[0028] When the ligand dspz is used to prepare the complex, the ligand dspz is added to a beaker containing ethanol and acetonitrile, stirred to dissolve, and the metal salt Fe(CF3SO3)2 is added, and the mixture is mixed and stirred evenly at room temperature to obtain a dark brown clear liquid. The solution is filtered and allowed to stand in a beaker for one week to obtain black rhombus crystals, which is the complex [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O.

[0029] The ligand dspz was fully dissolved in the mixed solvent of ethanol and acetonitrile to form a solution with uniform molecular distribution. The two nitrogen atoms (N) on the pyrazine ring firstly reacted with Fe 2+ The sulfur atom (S) and nitrogen atom (N) in the thiohydrazine group then coordinate with Fe 2+ Further coordination occurs, and as the reaction proceeds, the four Fe 2+ The ion and four dspz ligands gradually form a [2×2] node-like framework structure through multidentate coordination. Each dspz ligand bridges the adjacent Fe through a pyrazine ring and a thiohydrazine group. 2+ ions, forming a highly stable structure. After the coordination framework is formed, CF3SO 3- Anions, ethanol and water molecules further combine with the metal framework to form a crystal structure. By leaving the solution to stand for a week, ethanol and acetonitrile slowly evaporate, and the solution gradually reaches a supersaturated state, promoting the nucleation and growth of crystals, and ultimately forming black rhombus crystals.

[0030] Preferably, the molar ratio of dspz to Fe(CF3SO3)2 is 1:1; the usage ratio of dspz, ethanol and acetonitrile is: 0.19mmol-0.21mmol: 19mL-21mL: 19mL-21mL. The 1:1 molar ratio ensures that each dspz ligand can react with one Fe 2+ The ions are fully coordinated to avoid excess or deficiency of reactants. Ethanol and acetonitrile ensure that dspz and Fe(CF3SO3)2 are evenly distributed in the mixed solvent, promoting the complete reaction.

[0031] The third aspect of the present invention provides the application of a spin-regulated CO2 reduction catalytic material as described above in the field of artificial photosynthesis. The material is used as a core catalyst and combined with a photosensitive semiconductor (such as TiO2 or CdS) to construct an artificial photosynthesis photocatalytic reactor, which is suitable for indoor or outdoor CO2 conversion plants to convert CO2 in industrial waste gas or air into fuel.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention provides two complexes. The single crystal structure of complex 1 is [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O. It crystallizes in the triclinic Pī space group and presents a [2×2] grid structure. The complex is assembled by four ligands dopz and four Fe ions, and each Fe forms a N4O2 coordination environment. The average Fe-N bond length of Fe1 in complex 1 is Average Fe-N bond length of Fe2 Average Fe-N bond length of Fe3 Average Fe-N bond length of Fe4 Therefore, the coordination bond length analysis shows that the complex may have mixed valence, where Fe1 and Fe4 are Fe Ⅱ , Fe2, Fe3 are Fe Ⅲ , presenting a cis mixed valence structure.

[0034] (2) The single crystal structure of complex 2 is [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O. It crystallizes in the single crystal orthorhombic C2 / c space group. Four neutral ligands dspz are connected with four Fe to form a [2×2] node structure. Each Fe forms a coordination environment for N4S2. Complex 2 has four CF3SO 3– And one molecule of ethanol and three molecules of water participate in crystallization. Complex 2 has only one coordination environment of Fe ions, and the average bond length of Fe-N bond of Fe ions is

[0035] (3) The present invention successfully synthesized an iron metal tetranuclear cation cluster with a high spin state electronic structure through self-assembly technology. This cluster achieves the change of spin state by finely regulating the coordination microenvironment of the iron (Fe) site. This change of spin state has a significant effect on catalytic activity. The spin state of the catalytic center changes from Fe to 3+ When the low spin was changed to high spin, complex 1 showed more active CO2 photoreduction performance. After 4 hours of light irradiation, the CO yield of complex 1 reached 9.53 mmol g -1, which is four times more efficient than the corresponding low-spin metal grid. This significant improvement in activity shows that the photocatalytic performance can be effectively adjusted by regulating the spin state of the metal center, which has important guiding significance for the design of new and efficient photocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 X-ray crystal structures of complex 1 (a) and complex 2 (b);

[0038] Figure 2 Infrared spectra of complex 1 (a) and complex 2 (b);

[0039] Figure 3 Powder X-ray diffraction patterns of complex 1 (a) and complex 2 (b);

[0040] Figure 4 Thermogravimetric images of complex 1 (a) and complex 2 (b);

[0041] Figure 5 Magnetic susceptibility curves of complex 1 (a) and complex 2 (b);

[0042] Figure 6 Screening of photocatalytic solvent ratios for complexes 1 (a) and 2 (b);

[0043] Figure 7 The photocatalytic gas production of complex 1 (a) and complex 2 (b) changes with time;

[0044] Figure 8 This is the experimental diagram for controlling the photocatalytic performance of the complex;

[0045] Fig. 9 Cyclic voltammetry curves of complex 1 (a) and complex 2 (b) under different atmospheres;

[0046] Fig.10 Electrochemical impedance spectroscopy (EIS) of complex 1 (red) and complex 2 (blue). DETAILED DESCRIPTION

[0047] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a method for preparing a spin-controlled CO2 reduction catalytic material proposed by the present invention, its specific implementation method, characteristics and effects are described in detail as follows. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] The reagents involved in the experiment were from manufacturers such as Anage Chemical and Shanghai Lingfeng, and the details are shown in Table 1; the reagents involved were used directly without further purification.

[0049] Table 1 Reagents

[0050]

[0051] The equipment and instruments used in the experiment are shown in Table 2:

[0052] Table 2 Main instruments

[0053]

[0054]

[0055] Example 1

[0056] Preparation of ligand dopz: Place dihydrazide carbonate (0.45 g, 5 mmol) in a reaction bottle, add 30 mL of ethanol, stir to dissolve, then add 2-acetylpyrazine (1.22 g, 10 mmol), then drop 3-5 drops of glacial acetic acid, heat and stir at 80°C for 5 h. After the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a white powder product 2,2'-bipyrazine carbonate hydrazine.

[0057] Preparation of complex (1) [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O: Add ligand dopz (0.2mmol, 0.0396g) into a beaker containing 40mL acetonitrile, stir to dissolve, add metal salt Fe(CF3SO3)2 (0.2mol, 0.0728g), mix and stir evenly to obtain a wine red clear liquid. Filter, divide the filtrate into test tubes, place in a wide-mouth bottle containing isopropyl ether, and let stand for about a week to obtain black square crystals.

[0058] Example 2

[0059] Preparation of ligand dspz: Put thiomethylhydrazine (0.53 g, 5 mmol) into a reaction bottle, add 30 mL of ethanol, stir to dissolve, then add 2-acetylpyrazine (1.22 g, 10 mmol), then drop 3 to 5 drops of glacial acetic acid, heat and stir at 80°C for 5 h. After the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a light green powder product 2,2'-bipyrazinethiohydrazine.

[0060] Preparation of complex (2) [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O: Add ligand dspz (0.2mmol, 0.0396g) into a beaker containing 20mL ethanol and 20mL acetonitrile, stir to dissolve, add metal salt Fe(CF3SO3)2 (0.2mmol, 0.0728g), mix and stir evenly to obtain a dark brown clear solution. Filter the solution and let it stand in a beaker for about a week to obtain black rhombus crystals.

[0061] The crystallographic data of complexes (1) and (2) were obtained on a Bruker APEX-IICCD instrument equipped with graphite monochromatic radiation Mo Kα Collected at the corresponding temperature. Data collection, data reduction and unit optimization were performed using two program packages, Bruker Instrument Servicev4.2.2 and SAINT V8.34A. The structure of the complex was analyzed using the SHELXS program package, and the crystal data was optimized using the full matrix least squares method using the SHELXL program package. Absorption correction was performed using the multi-scan program package SADABS. The hydrogen atoms of the organic ligands were anisotropically optimized on F2 using the riding mode on the SHELXTL program package. The crystallographic data of the complex are shown in Table 3.

[0062] Table 3 Crystallographic parameters of the complexes

[0063]

[0064] a R1=Σ(||F0|-|Fc||) / Σ|F0|; b wR2=[Σw(|F0 2 |-|Fc 2 |) 2 / Σw|F0 2 | 2 ] 1 / 2 ; c GOF=

[0065] [∑[w(F0 2 -Fc 2 ) 2] / (Nobs-Nparams)] 1 / 2 , based on the data I>2σ(I).

[0066] The single crystal structure of complex 1 is [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O, crystallized in the triclinic Pī space group, presenting a [2×2] grid structure, and the unit cell parameters of the complex are α=87.315(2)°, β=82.628(2)°, γ=87.616(2)°, Z=2, The complex is composed of four ligands dopz and four Fe ions, each of which forms a coordination environment for N4O2. The average Fe-N bond length of Fe1 in complex 1 is Average Fe-N bond length of Fe2 Average Fe-N bond length of Fe3 Average Fe-N bond length of Fe4 Therefore, the coordination bond length analysis shows that the complex may have mixed valence, where Fe1 and Fe4 are Fe Ⅱ , Fe2, Fe3 are Fe Ⅲ , presenting a cis mixed valence structure.

[0067] The single crystal structure of complex 2 is [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O, crystallized in single crystal orthorhombic C2 / c space group, and the unit cell parameters of the complex are α=90°, β=107.039(3)°, γ=90°, Z=4, The complex consists of four neutral ligands dspz connected to four Fe to form a [2×2] node structure, and each Fe forms a coordination environment for N4S2. Complex 2 has four CF3SO 3– And one molecule of ethanol and three molecules of water participate in crystallization. Complex 2 has only one coordination environment of Fe ions, and the average bond length of Fe-N bond of Fe ions is

[0068] Infrared absorption spectroscopy analysis: Figure 2 As shown, complexes 1 and 2 have -1 The medium-strong peak at is the anion CF3SO 3- The absorption peak is between 1605 and 1615 cm -1 The absorption peak appearing at is the stretching vibration peak of the Schiff base C=N bond.

[0069] Powder X-ray diffraction analysis: Figure 3As shown in (a), there is a good agreement between the crystalline powder X-ray diffraction pattern of complex 1 (represented by the red spectrum) and the simulated diffraction pattern calculated based on the single crystal structure (represented by the black spectrum), which confirms that complex 1 is a pure crystalline phase. Figure 3 (b) shows the agreement between the crystalline powder X-ray diffraction data (red spectrum) and the simulated diffraction pattern (black spectrum) of complex 2, further confirming the purity and crystal structure of complex 2. Although there are differences in the intensity of the diffraction peaks, which may be due to the preferred orientation effect of the powder sample, the consistency of the peak position still shows that the experimental data is highly consistent with the theoretical model.

[0070] Thermogravimetric analysis: Figure 4 As shown in (a), thermogravimetric analysis (TGA) of complex 1 revealed that it experienced an obvious weight loss stage in the temperature range of 50-330°C, with a total reduction of 4.59%. This is mainly attributed to the gradual removal of solvent molecules, including acetonitrile and water molecules, in the crystal lattice of complex 1. As the temperature further increased to 340°C, the molecular structure of complex 1 began to undergo significant thermal degradation, resulting in a sharp decrease in its structural stability. Ultimately, after completing the entire thermal decomposition process, the remaining mass of complex 1 was 22.01%, which may represent its thermally stable skeleton or decomposition product. Similarly, Figure 4 (b) shows the thermogravimetric analysis results of complex 2. At a relatively low temperature of 64°C, the weight of complex 2 began to slowly decrease, a change attributed to the gradual evaporation and removal of the crystallization solvent ethanol and water molecules in its lattice. As the temperature continued to rise, starting from 300°C, the molecular structure of complex 2 also began to undergo thermal degradation. At 450°C, the structure of complex 2 had completely collapsed, marking the limit of its thermal stability.

[0071] Magnetic susceptibility curve analysis: Figure 5 As shown in (a), the temperature-dependent magnetic susceptibility test of complex 1 covers the entire temperature range from 2 to 300 K. At an extremely low temperature of 2 K, the molar magnetic susceptibility of complex 1, χ M T starts at 1.101cm3 / mol K, indicating that it has significant magnetic properties. When the temperature rises to 60K, the magnetic susceptibility enters a plateau period, and χ M The T value reaches 8.014 cm3 / mol K, which may indicate a special spin arrangement or interaction. As the temperature is further increased, the magnetic susceptibility gradually increases until at 300 K, χ M The T value rises to 15.656 cm3 / mol K, and the changes in the entire temperature range show an incomplete spin crossover (SCO) phenomenon, which may be related to the spin state change of the metal center in complex 1. Figure 5(b) describes the magnetic susceptibility behavior of complex 2. At 300K, the χ M The T value is 1.8 cm3 / mol K, which is higher than the theoretical value (1.5 cm3 / mol K) of four low-spin Fe3+ (s=1 / 2), indicating the contribution of orbital magnetic moment. As the temperature decreases, the magnetic susceptibility gradually decreases, which suggests that complex 2 has the characteristics of antiferromagnetic coupling. At 29K, χ M The T value drops sharply to 0.8 cm3 / mol K, which may mark a magnetic phase transition. Based on the magnetic susceptibility data, it can be determined that the electronic structure of Fe ions in complex 2 changes to low-spin paramagnetic Fe3+ (s=1 / 2) at this temperature and is in an antiferromagnetic coupling state.

[0072] Photocatalytic solvent ratio screening analysis: The solvent ratio was screened by adding the complex as a catalyst (1 mg) into the photocatalytic reaction container, using tri(2,2-bipyridyl)ruthenium(II) chloride hexahydrate (RuPS) (1 mg) as the photosensitizer, and 1,3-dimethyl-2-phenylbenzimidazolidine (14 mg) as the sacrificial agent. The solvent system was a mixed solution of acetonitrile and water. CO2 was introduced into the photocatalytic system for 15 min. Under a light intensity of 100 mW cm -2 Irradiate for 5 hours, and perform gas chromatography analysis after the irradiation. Figure 6 As shown, when the solvent ratio was adjusted to a volume ratio of acetonitrile to water of 4.7:0.3, complexes 1 and 2 exhibited the best catalytic effect in the CO2 photocatalytic reduction reaction.

[0073] Analysis of the change of photocatalytic gas production over time: Figure 7 As shown, the gaseous products such as CO and H2 were carefully analyzed by gas chromatography, while the liquid products were detected by ion chromatography, but only a small amount of HCOOH was found. In the CO2 reduction reaction, as the illumination time increased, the catalytic activity of complex 1 reached a stable state after 4 hours. In contrast, the gas production of complex 2 increased slowly. When complex 1 was used as a photocatalyst, its yield reached 9.53 mmol g after the initial 4 hours of illumination. -1 When complex 2 was used as a catalyst under the same conditions, the CO yield was low, only 2.12 mmol g -1 This comparison highlights the higher efficiency and activity of complex 1 in the photocatalytic CO2 reduction reaction.

[0074] Analysis of the photocatalytic performance control experimental diagram: Figure 8As shown, in the absence of complexes 1 and 2, only trace amounts of CO and H2 were detected in the experiment. This indicates that without the participation of an effective photocatalyst, the efficiency of the CO2 photoreduction reaction is extremely low. In further experiments, no products were detected in the absence of photosensitizers, sacrificial agents, or light irradiation, a result that highlights the central role of these components in promoting the CO2 photoreduction process. When Ar gas was used instead of CO2, only trace amounts of gas were detected, further confirming that the participation of CO2 is essential for the reaction. In addition, by comparative experiments, only trace amounts of CO were detected using equimolar FeCl2 and FeCl3 as reference catalysts. The results of these control experiments indicate that the detected CO production is mainly achieved through the photocatalytic action of CO2 on the metal grid molecular catalyst, rather than through the thermal or chemical decomposition of organic matter.

[0075] Analysis of cyclic voltammetry curves under different atmospheres: Fig. 9 As shown in the figure, in order to further explore the electron transfer mechanism in the photocatalyst and CO2 reduction process, we conducted cyclic voltammetry (CV) tests on complexes 1 and 2 in Ar and CO2 atmospheres. In Ar atmosphere, both complexes showed three significant reduction peaks, corresponding to the Fe 3+ / Fe 2+ , Fe 2+ / Fe +1 and Fe +1 / Fe 0 However, under CO2 atmosphere, the CV curve of complex 2 showed only a slight current change, indicating that its electron transfer activity with CO2 was relatively low. On the contrary, the CV curve of complex 1 under CO2 atmosphere showed obvious redox peak shift, especially a higher reduction potential characteristic peak at 0.89V, which showed that complex 1 had higher activity in catalyzing CO2 reduction.

[0076] Electrochemical impedance spectroscopy (EIS) analysis: Fig.10 As shown, the radius of the curved surface of complex 1 is smaller than that of complex 2, and this feature means that the impedance of charge transfer in complex 1 is lower. In electrochemical and photocatalytic processes, the efficiency of charge separation and transfer is one of the key factors that determine catalytic performance. A smaller arc radius is usually associated with faster charge mobility because the charge is transferred over a shorter path, thereby reducing the energy consumption and possible recombination opportunities during the transfer process. Therefore, complex 1 can more effectively separate and transfer photogenerated charge carriers due to its lower charge transfer impedance, which helps to improve its photocatalytic activity. This efficient charge separation and transfer ability enables complex 1 to exhibit better performance in light-driven chemical reactions, especially in applications that require fast charge transfer.

[0077] The present invention successfully synthesized an iron metal tetranuclear cation cluster through self-assembly technology. The cluster has a high spin state electronic structure and can precisely control its spin state by adjusting the coordination environment of the iron ion (Fe) site. This control strategy significantly improves the activity of the cluster in the CO2 photoreduction reaction, so that the CO yield can reach 9.53mmol g within a 4-hour reaction time. -1 , which is 4 times higher than that of the low-spin metal grid. This research result not only demonstrates the possibility of enhancing photocatalytic performance by adjusting the spin state of metal centers, but also provides valuable guidance for the design of future photocatalysts.

[0078] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A spin-regulated CO2 reduction catalytic material, wherein the single crystal structure formula of the material is: [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O or [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O; wherein, dopz is 2,2'-dipyrazine hydrazine carbonate; dspz is 2,2'-dipyrazine thiohydrazine.

2. The spin-regulated CO2 reduction catalytic material according to claim 1, characterized in that: The single crystal structure has a molecular formula of [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O, and is crystallized in the triclinic system. P ī space group, presenting a [2×2] grid structure. The complex is assembled by four ligands dopz and four Fe ions, and each Fe forms a N4O2 coordination environment. In complex 1, the average Fe‒N bond length of Fe1 is 2.143 Å, the average Fe‒N bond length of Fe2 is 1.971 Å, the average Fe‒N bond length of Fe3 is 1.987Å, and the average Fe‒N bond length of Fe4 is 2.118 Å.

3. The spin-regulated CO2 reduction catalytic material according to claim 1, characterized in that: The single crystal structure formula is [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O, crystallized in single crystal orthorhombic system C 2 / c Space group, four neutral ligands dspz are connected with four Fe to form a [2×2] node structure, each Fe forms a coordination environment for N4S2; complex 2 has four CF3SO3 – One molecule of ethanol and three molecules of water participated in the crystallization. The average bond length of the Fe‒N bond of Fe ions in complex 2 was 1.952Å.

4. A method for preparing a spin-regulated CO2 reduction catalytic material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Preparation of organic ligand dopz: put dihydrazide carbonate in a reaction bottle, add ethanol, stir to dissolve, then add 2-acetylpyrazine, then drop glacial acetic acid, heat and stir, after the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a white powder product; S2. Preparation of organic ligand dspz: put thiomethylhydrazine into a reaction bottle, add ethanol, stir to dissolve, then add 2-acetylpyrazine, then drop glacial acetic acid, heat and stir, after the reaction is completed, cool to room temperature, filter, and vacuum dry to obtain a light green powder product; S3. Preparation of complex: Add the ligand dopz prepared in step S1 or the ligand dspz prepared in step S2 into a beaker containing acetonitrile / acetonitrile and ethanol, stir to dissolve, add metal salt Fe(CF3SO3)2, mix and stir evenly at room temperature, filter, and let stand for one week to obtain complex crystals.

5. A method for preparing a spin-regulated CO2 reduction catalytic material as claimed in claim 4, characterized in that: In step S3, When the ligand dopz is used to prepare the complex, the ligand dopz is added to a beaker filled with acetonitrile, stirred to dissolve, and the metal salt Fe(CF3SO3)2 is added, mixed and stirred evenly at room temperature to obtain a wine red clear liquid, and the filtrate is evenly divided into test tubes after filtration, placed in a wide-mouth bottle filled with isopropyl ether, and allowed to stand for one week to obtain black square crystals, which is the complex [Fe4(dopz)4](CF3SO3)4·3MeCN·H2O; When the ligand dspz is used to prepare the complex, the ligand dspz is added to a beaker containing ethanol and acetonitrile, stirred to dissolve, and the metal salt Fe(CF3SO3)2 is added, and the mixture is mixed and stirred evenly at room temperature to obtain a dark brown clear liquid. The solution is filtered and allowed to stand in a beaker for one week to obtain black rhombus crystals, which is the complex [Fe4(dspz)4(CF3SO3)4]·EtOH·3H2O.

6. The method for preparing the spin-regulated CO2 reduction catalytic material according to claim 4, characterized in that: In step S1, the molar ratio of the carbonate dihydrazide to the 2-acetylpyrazine is 1:2, and the volume ratio of the ethanol to the glacial acetic acid is: 49.9 mL ~ 50.1 mL: 0.15 mL ~ 0.25 mL.

7. The method for preparing the spin-regulated CO2 reduction catalytic material according to claim 4, characterized in that: In step S2, the molar ratio of the thiomethylhydrazine to the 2-acetylpyrazine is 1:2, and the volume ratio of the ethanol to the glacial acetic acid is: 49.9 mL ~ 50.1 mL: 0.15 mL ~ 0.25 mL.

8. The method for preparing the spin-regulated CO2 reduction catalytic material according to claim 5, characterized in that: When the ligand dopz is used to prepare the complex, the molar ratio of the dopz and the Fe(CF3SO3)2 is 1:1; the usage ratio of the acetonitrile and the dopz is: 39 mL ~ 41 mL: 0.19 mmol ~ 0.21 mmol.

9. The method for preparing the spin-regulated CO2 reduction catalytic material according to claim 5, characterized in that: When the ligand dspz is used to prepare the complex, the molar ratio of the dspz and the Fe(CF3SO3)2 is 1:1; the usage ratio of the dspz, the ethanol and the acetonitrile is: 0.19 mmol ~ 0.21 mmol: 19 mL ~ 21 mL: 19 mL ~ 21 mL.

10. Use of the spin-regulated CO2 reduction catalytic material according to any one of claims 1 to 3 in the field of artificial photosynthesis.

Citation Information

Patent Citations

  • Bis(2-acetylpyrazine) thiocarbonohydrazone and preparation method and application of bismuth (III) complex thereof

    CN102977038A

  • Thiourea Schiff base binuclear copper complex as well as preparation method and application thereof

    CN118255786A